2016
DOI: 10.1167/16.10.20
|View full text |Cite
|
Sign up to set email alerts
|

Interocular suppression patterns in binocularly abnormal observers using luminance- and contrast-modulated noise stimuli

Abstract: In binocular viewing, images presented to the amblyopic eye are suppressed in the cortex to prevent confusion or diplopia. The present study measures depth and extent of interocular suppression across the central circular 24° visual field in observers with strabismus and microstrabismus. Visual stimuli were concentric rings of alternating polarity, each divided into sectors. Rings were defined by luminance (L), luminance-modulated noise (LM), or contrast-modulated noise (CM). They were viewed binocularly excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 85 publications
5
27
1
Order By: Relevance
“…Patient LW, who had mild amblyopia, showed equal suppression between eyes, which is consistent with previous studies reporting positive correlations between amblyopia severity and suppression strength. [4][5][6][7][8][9] Overall, however, we did not observe significant correlations between suppression of the amblyopic eye and clinical measures of amblyopia severity. The extensive testing time required in this study limited our sample size and CFS noise contrast also varied within the amblyopic group; therefore, the correlation results should be interpreted cautiously (see Supplementary Results for further details).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Patient LW, who had mild amblyopia, showed equal suppression between eyes, which is consistent with previous studies reporting positive correlations between amblyopia severity and suppression strength. [4][5][6][7][8][9] Overall, however, we did not observe significant correlations between suppression of the amblyopic eye and clinical measures of amblyopia severity. The extensive testing time required in this study limited our sample size and CFS noise contrast also varied within the amblyopic group; therefore, the correlation results should be interpreted cautiously (see Supplementary Results for further details).…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies using dichoptic global motion, 4,44 phase matching, 5,45 and other contrast-or luminance-balancing suppression measures 6,8 report greater average suppression in patients with amblyopia than controls. However, these previously established methods (including the dichoptic global motion test used in this study) measure the interocular balance of suppression and do not account for monocular deficits.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Current models of both normal and abnormal binocular vision suggest that binocular performance reflects a balance between suppression and excitation between eyes (Baker, Meese, & Hess, 2008;Ding, Klein, & Levi, 2013a;Ding, Klein, & Levi, 2013b). Previously we found that interocular suppression in amblyopes was luminance-polarity dependent, with luminance increments (or white stimuli) being suppressed more strongly than luminance decrements (or black stimuli) (Chima et al, 2016). A polarity dependence was not noted for interocular suppression generated with unilateral blur, which was broad, extending across the central 24°field (Chima et al, 2015).…”
Section: Introductionmentioning
confidence: 68%
“…To prevent confusion (where two different objects are perceived at the same location) or diplopia (where one object is perceived at two different locations), one image is cortically suppressed (Sengpiel, Blakemore, Kind, & Harrad, 1994). Interocular suppression is present in amblyopia (e.g., Black, Thompson, Maehara, & Hess, 2011;Chima, Formankiewicz, & Waugh, 2016;Irvine, 1948;Li et al, 2013;Mehdorn, 1989;Travers, 1938). It is also present in observers with normal binocular vision, when binocularly viewing stimuli in the presence of unilateral blur (Chima, Formankiewicz, & Waugh, 2015;Pianta & Kalloniatis, 1998;Simpson, 1991) or when a neutral density (ND) filter is placed before one eye (Baker, Meese, Mansouri, & Hess, 2007;Li et al, 2012;Li et al, 2013;Zhang, Bobier, Thompson, & Hess, 2011;Zhou, Jia, Huang, & Hess, 2013).…”
Section: Introductionmentioning
confidence: 99%